Pharmaceutical botany - Youngken, Heber W.; Stewart, F. E. (Philadelphia, Pennsylvania : P. Blakiston's Son & Co., 1914)
The aim has been to eliminate from this book all those topics that are minor importance to the student and practitioner of Pharmacy. As a pharmacist and teacher, the writer feels that the botanical preparation for Pharmacognosy and Materia Medica, in those colleges where Botany is given for one year, should include mainly the structural and systematic aspects of the science.
Part I. Terminology and Morphology -- Part II. Taxonomy.
Includes index.
Keywords: PHARMACY